A legal analysis of sobriety checkpoints - Vaughn, Michael S. (American journal of criminal justice, 1990)
Law enforcement agents are asked to help solve problems involving alcohol abuse in a society exhibiting reluctance to change its attitude about drinking and driving. As the public’s concern over drunken driving intensifies, use of the sobriety checkpoint is becoming a major law enforcement/public policy issue. Recent case law upholds use of the checkpoint in order to deter and detect the drunken driver. Although the United States Supreme Court has not directly ruled on the constitutionality of the sobriety checkpoint, there is a considerable body of state case law upholding its validity. Generally, with some exceptions, sobriety checkpoints appear to be constitutional if law enforcement agents follow proper guidelines and procedures. This paper analyzes case law pertaining to checkpoints, and gives law enforcement agencies direction in establishing constitutionally sound sobriety checkpoints, in conclusion, the article synthesizes roadblock and sobriety checkpoint law to provide law enforcement officers a plan for proper checkpoint construction.